Synthesis and in vitro antioxidant evaluation of new bis(-aminoalkyl)phosphinic acid derivatives - Sarac, Kamiran; Orek, Cahit; Cetin, Ahmet; Dastan, Taner; Koparir, Pelin; Dastan, Sevgi Durna; Koparir, Metin (Taylor & Francis Ltd, 2016)
Diamines were added to arylaldehydes in ethanol, which resulted in corresponding diimines. Novel bis-1-aminophosphinic acid compounds were synthesized through the interaction of diimines and hypophosphorous acid. The new compounds were characterized by elemental analyses, FT-IR and H-1, C-13 and P-31 NMR techniques. The in vitro antioxidant activity of the newly synthesized compounds were measured and found to exhibit significantly higher antioxidant activity than the standard.
Keywords: Aldehydes; amines; 1-aminophosphinic acids; antioxidant activity